UPAYA HUKUM YANG DILAKUKAN KORBAN KEJAHATAN DIKAJI DARI PERSPEKTIF SISTEM PERADILAN PIDANA DALAM PUTUSAN MAHKAMAH AGUNG RI - Lilik Mulyadi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2012)
Positive Legal Indonesia provides protection against crime victims who are not directly in the Penal Code, Criminal Procedure Code, as well as outside the Criminal Code and Criminal Procedure Code. Later in the Code of Criminal Procedure formulatif policies and by laws to understanding the victim used different terminology, namely the complainant, the complainant, witnesses, interested third parties and the injured party. In practice, the request made by the applicant with the PK as the quality of the witnesses, interested third parties, the Legal Adviser or by the Public Prosecutor and apparently only remedy reconsideration made by the Public Prosecutor and Third Party concerned (Judicial Review Decision No. 4 PK / PID/2000 November 28 2001), which was granted by the Supreme Court while the petition for judicial review filed applicant witnesses (Judicial Review Decision No. 11 PK/PID/2003 August 6, 2003), or the reporting witness stated by the Supreme Court was not accepted by because the applicant is not qualified to appeal judicial review. From the theoretical dimension turns doing different interpretations of the Supreme Court as provided Art. 263 paragraph (1) Criminal Procedure Code that the applicant is granted a judicial review conducted by the Public Prosecutor and the Third Party concerned on the one hand while on the other side of the applicant's application for judicial review of quality reporting victims or witnesses can not be accepted. Keywords: remedies, victims of crime, judicial review